Orientaciones astronómicas en la arquitectura de Mesoamérica: Oaxaca y el Golfo de México - Francisco Sánchez Nava, Pedro (Prostor, kraj, čas, 2015)
This monograph presents the results of a systematic study of orientations in prehispanic architecture of two sub-areas of Mesoamerica. The alignment data for a number of civic and ceremonial buildings were collected with field measurements at 42 archaeological sites in the cultural regions of Oaxaca and the Gulf of Mexico.